The Perception of Artificial Intelligence on Students in Nuan Courses - Azzam, Muhammad Muhyiyuddin; tsalisa, Ghefira; Mujayanah, Kholistul; Putri, Salsa Billa Nurmala; Sholikhah, Novi Nurma Wahidatus; Amalia, Lisa; Fatimah, Siti (Proceeding International Conference on Religion, Science and Education, 2025)
This study aims to analyze the effect of artificial intelligence (AI) on students' understanding in the NU course at IAINU Kebumen. The method used is quantitative analysis with a survey research design. Data were collected through questionnaires distributed to 100 students taking the course. The variables studied included the effectiveness of using AI in learning, learning motivation, and academic outcomes. In addition, there was a positive relationship between learning motivation and academic outcomes of students using AI. These findings contribute to the development of learning methods in the field of NU, as well as encouraging the integration of technology in higher education. This study is expected to be a reference for teachers and educational institutions to utilize artificial intelligence as a tool in the teaching and learning process.